1999
DOI: 10.1093/cercor/9.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Increased Receptive Field Size in the Surround of Chronic Lesions in the Adult Cat Visual Cortex

Abstract: Visual cortical lesions destroy the target cells for geniculocortical fibers from a certain retinotopic region. This leads to a cortical scotoma. We have investigated the receptive fields of cells in the visual cortex before, 2 days and 2 months after focal ibotenic acid lesions in the adult cat visual cortex and have found signs of receptive field plasticity in the surroundings of the chronic but not the acute and subacute excitotoxic lesions. In the subacute state (first two days post lesion) receptive field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 40 publications
(47 reference statements)
6
59
0
1
Order By: Relevance
“…Other work using electrophysiological techniques also finds that peri-infarct tissue moves relative to the infarct location. (Eysel and Schweigart, 1999;Frost et al, 2003;Jenkins and Merzenich, 1987;Reinecke et al, 2003;Schiene et al, 1999;Zepeda et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work using electrophysiological techniques also finds that peri-infarct tissue moves relative to the infarct location. (Eysel and Schweigart, 1999;Frost et al, 2003;Jenkins and Merzenich, 1987;Reinecke et al, 2003;Schiene et al, 1999;Zepeda et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that the compensatory improvements in skilled behavior that occur in the chronic period may be associated with long-lasting plastic changes in residual tissue including changes in neuronal structure, cortical organization, neurotrophic factor regulation, and electrophysiological responsiveness (Eysel and Schweigart, 1999;Schiene et al, 1999;Frost et al, 2003;Gonzalez and Kolb, 2003;Reinecke et al, 2003;Fridman et al, 2004;Zepeda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, partial optic nerve damage or cortical tissue loss may lead to a reduced physiological signaling power and to a loss of firing synchrony of neuronal assemblies, thus increasing processing time. Secondly, there is an extensive remapping and reorganization of the visual field representation after pre-and post-chiasmatic damage as shown in animal model studies [34][35][36][37], as well as behavioral [38] and fMRI studies in patients [31][32][33]39]. Such receptive field reorganization is believed to be mediated by mechanisms involving plasticity of intrinsic cortical horizontal connections [40].…”
Section: Perceptual Deficits In the ''Intact'' Visual Field Of Patientsmentioning
confidence: 99%
“…Less is known about how the visual system remaps to cover the visual field after injury to area V1 or its input projection from the lateral geniculate nucleus (LGN). Enlarged receptive fields have been found in areas surrounding chronic V1 lesions in cats (20)(21)(22), and visual point spread functions were seen to enlarge over time in the areas surrounding focal V1 lesions in kittens (23). Smaller, shortterm changes (2 d after the lesion) have been reported as well (24).…”
mentioning
confidence: 99%